Peran Generasi Milenial dan Gen Z dalam Mendorong Pertumbuhan E-Commerce Halal di Indonesia - Febiola Anggun Tri Setyo; Zumrotul Latifah; Ahmad Sidiq; Isma Thayyibah Hanun; Afaful Ummah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study analyzes the role of millennials and Gen Z in driving the growth of halal e-commerce in Indonesia. The global halal industry is projected to reach US$3.36 trillion by 2028, underscoring the importance of strengthening halal e-commerce in Indonesia, which has the largest Muslim population in the world (Kawsar, 2025). Millennials and Gen Z are the dominant users of the internet and digital marketplaces, thus playing a strategic role in expanding the digital halal economic ecosystem. This study uses a qualitative approach with literature studies and in-depth interviews with consumers and halal digital business actors. The analysis focuses on digital behavior, halal product preferences, and awareness of sharia economic principles. The results show that millennials and Gen Z contribute through three main roles. First, as smart consumers who show high preference and loyalty to certified halal products. Second, as creative business actors who create sharia startups and marketplaces with innovative digital marketing strategies. Third, as agents of change who promote digital halal literacy and strengthen public awareness of the importance of halal products and services. In conclusion, the role of these two generations is not only in consumption, but also in creating a sustainable digital halal business ecosystem, strengthening Indonesia's competitiveness in the global halal industry, and supporting national sharia economic development.